2011
DOI: 10.4103/2231-0746.83145
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 4% articaine hydrochloride and 2% lignocaine hydrochloride in the extraction of maxillary premolars for orthodontic reasons

Abstract: Background:Articaine is an amide local anesthetic that differs from other agents of its group due to the presence of a thiophene ring instead of a benzene ring, and it is one of the commonly used local anesthetic agents for day care surgeries. Some researches claim that articaine is superior to lidocaine in its biologic profile.Purpose:To evaluate the efficacy, time of onset of anesthesia, duration of action and intra- or post-administration complications of articaine in comparison with lignocaine for bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 4 publications
(5 reference statements)
5
20
0
Order By: Relevance
“…5 Also, rapid diffusion in to the tissues owing to its high lipid solubility is also responsible for quicker onset of action. This has been proved in the previous studies by Hassan et al 8 and costa et al 9 and our study confirms the same. In our study statistically significant variation between the two agents was observed in terms of onset of anaesthesia.…”
Section: Onset Of Actionsupporting
confidence: 93%
See 1 more Smart Citation
“…5 Also, rapid diffusion in to the tissues owing to its high lipid solubility is also responsible for quicker onset of action. This has been proved in the previous studies by Hassan et al 8 and costa et al 9 and our study confirms the same. In our study statistically significant variation between the two agents was observed in terms of onset of anaesthesia.…”
Section: Onset Of Actionsupporting
confidence: 93%
“…The mean duration of anaesthesia in our study was 128 ± 15.31 min for articaine group and 86 ± 13.14 min for the lignocaine group which statistically confirms (P <0.001) that 4% articaine has a longer duration of action when compared to 2% lignocaine. This was in accordance with the previous studies by Hassan et al 8 and Costa et al 9 Although the mean duration of anaesthesia for both the articaine and lignocaine in the current study was found to be prolonged than the previously mentioned studies, all the three studies showed significant differences with longer duration of action for articaine. This can be attributed to better plasma protein binding 5 of articaine (95%) compared to lignocaine (65%).…”
Section: Duration Of Anaesthesiasupporting
confidence: 93%
“…Hassan et al [4] conducted an in vivo study to assess the effectiveness of LAdr and articaine in bilateral maxillary premolars extraction. They found in their study that for all the patients in articaine group they did not require palatal injection because of its remarkable diffusion property, whereas in lignocaine group they required an additional palatal injection for palatal soft tissue anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting diffusion of LA agent are keratinized or nonkeratinized type of mucosa, mucosal vessels and porosity of bone. Hasan et al [4] reported that 4 % articaine has good quality of diffusion compared to 2 % lignocaine. Although lignocaine has a poor diffusion property, it is already established and there is limited available data regarding the diffusion property of ropivacaine.…”
Section: Introductionmentioning
confidence: 98%
“…The significantly faster onset of action with 4% articaine in our study can be attributed to the presence of a thiophene ring in its structure enabling it to be more lipophilic is similar to the study results of Hassan et al . [ 13 ] Oertel et al . [ 14 ] in a study comparing concentration of 4% articaine and 2% lignocaine showed higher blood levels for articaine in alveolus blood because of higher concentration of 4% articaine when compared with 2% lignocaine in the injection solution.…”
Section: Discussionmentioning
confidence: 99%